DEKONSTRUKSI TOKOH DALAM NOVEL ATHEIS KARYA ACHDIAT KARTA MIHARDJA - Rohana Rohana (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2021)
The aim of this research is to reveal the deconstruction of male characters in the novel Atheis by Achdiat Karta Mihardja. The method that will be used by researchers in this research is descriptive method. The data collection technique that the writer uses in this research is the content analysis technique. The analysis technique in this research is (1) Identifying the oppositional hierarchy in the text, which usually shows which terms are systematically privileged and which are not. (2) The oppositions are reversed by showing the interdependence between the opposites or their privacy is reversed, and (3) introducing a new term or idea which apparently cannot be included in the old oppositional category. The results showed that ultimately the Atheists believed in God and regretted what they believed so far.